Edukasi integrasi dan kolaborasi pekerjaan administratif menggunakan google docs bagi siswa SMK Perdana I - Maulana, Yoppy Mirza; Arnandy, Didiet Anindita (Universitas Pendidikan Indonesia (UPI), 2024)
In the information age, computers play an important role in supporting administrative work in organizations. Computers are tools that have great potential to realize the efficiency and effectiveness of administrative work. With computers via an office application software (OAS), administrative work can be carried out in an integrated and collaborative manner. Integration is merging or blending into something whole, while collaboration is the activity of working together with other people to achieve maximum results. However, in fact there are still users who use applications that are not integrated or collaborated, resulting in inefficiency and effectiveness in carrying out administrative work. The OAS that can support the integration and collaboration process is Google Docs. Google Docs is an internet-based OAS that can be used via a computer or Android-based cellphone. Based on the importance of integration and collaboration in administrative work using Google Docs, this service aims to provide education. This education is aimed at students at SMK Perdana I Surabaya majoring in office automation by the needs of the school principal. This education resulted in an increase in insight and practice for 16 participants from 20 or 80%.